Exchange rates and exports: evidence from manufacturing firms in the UK - Zhang, Xufei (2008)
The thesis examines the effect of exchange rate variability on firms' export decisions, using data for UK manufacturing firms. We separately investigate the relationship between the changes of level of exchange rate and exports and that between exchange rate uncertainty and exports. Our results show that export extensive margin is not significantly related to changes in the level of exchange rates, whereas exchange rates have a significant and negative impact on the export intensity. Since industry heterogeneity is important in the effect of exchange rate level changes, we further explore possible explanations. In particular, we test whether external orientation and market structure play a role in the effect. Our results provide significant evidence for the role of external orientation and market structure. We also find significant evidence for the hysteresis effect of exchange rate uncertainty on exports, using new measures of uncertainty. In both cases, the behaviour of multinationals is investigated. We find that multinationals are less likely to be negatively affected by both changes of level of exchange rate and exchange rate uncertainty than indigenous firms.